Study on Isolation of Organism and Antibiotic Sensitivity Pattern in Blood Culture of Enteric Fever Patients in a Tertiary Care Hospital in Bangladesh - Barman, Tushar Kanti; Uddin, Iftekhar; Haque, Md Ahsanul; Haque, Md Monjurul; Paul, Nandita (Mugda Medical College Journal, 2025)
A cross-sectional, observational study was conducted in the Department of Medicine, Mugda Medical College Hospital, Dhaka, Bangladesh, between March 2022 and September 2023, to observe the changing pattern of antibiotic sensitivity pattern among enteric pathogens causing enteric fever. A total of 50 blood culture and sensitivity reports were analyzed. Blood samples were derived from 50 patients included in this study, who were admitted into the medicine inpatient department of Mugda Medical College Hospital suffering from fever for at least 2 weeks and were confirmed having enteric fever. The predominant growth of two bacteria was observed in all (100%) samples. The most common organisms isolated were Salmonella typhi as typhoid fever pathogens and Salmonella paratyphi A as paratyphoid fever pathogens; these represented 88% and 12% of isolates respectively. Salmonella typhi organisms were found 100% sensitive to amoxycillin, trimethoprim-sulfamethoxazole, chloramphenicol, gentamicin, meropenem, cefepime, followed by imipenem (85%), ampicillin (81%), ceftriaxone (78%), levofloxacin (77%) and cefuroxime (77%). However, amoxicillin, trimethoprimsulfamethoxazole, ceftazidime, cefotaxime, ceftriaxone and chloramphenicol were found 100% sensitive to paratyphoid pathogens. Very high rate of resistance was seen against nalidixic acid (88%), piperacillin-tazobactam (50%), azithromycin (47%), co-amoxiclav (40%) and doxycycline (40%) in salmonella typhi infections, while nalidixic acid and azithromycin were found 100% resistant to Salmonella paratyphi A infection. Mugda Med Coll J. 2024; 7(2): 108-113